DEVELOPING STUDENTS’ LISTENING COMPREHENSION BY APPLYING BOTTOM-UP TECHNIQUE - Suparlan, Suparlan (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2022)
The aim of this study was to depelove students’ listening comprehension by applying Bottom-Up technique. This study is a classroom action research which has done in three cycles. The subject of the study was the eight grade of the students of MTs. Darul Aminin NW Aikmual Lombok Tengah. The study was conducted by applying Bottom-Up technique which consists of three main stages. There are word processing, phrase processing, and comprehension. The writer observed students’ depelovement in listening comprehension by collecting data through field notes, observation checklist and listening test. Field note and observation checklist were used to gather the students’ attitude in learning process. The data of listening was collected through listening test and it was assessed through scoring rubric. The result showed that students’ problems in understanding the contents of listening and vocabulary had been solved by applying Bottom-Up technique. In the third cycle, the students mean score was 83.7. It increased in the second cycle to 82.1, and 76.7 in first cycle. As the conclusion, the technique was able to be applied in depeloving students’ listening comprehension. As a technique in teaching and learning process, the writer recommends the teacher to apply Bottom-Up technique.